THE THEME OF THE “LITTLE MAN” IN RUSSIAN LITERATURE: YESTERDAY AND TODAY - Ramazonova Nozima Farkhod kizi (International Journal of Literature and Language Studies, 2026)
This article examines the evolution of the theme of the “little man” in Russian literature from its origins to the present day. The study explores the formation of the literary archetype of the “little man,” its typological characteristics, and its significance within the Russian literary tradition. Special attention is given to the social, historical, and cultural factors that contributed to the emergence of this character type. The article traces the development of the image of the “little man” from early Russian literature and eighteenth-century journalism to the works of A.S. Pushkin, N.V. Gogol, F.M. Dostoevsky, and the writers of the Natural School. The research analyzes the conflict between the individual and society, highlighting how social inequality shapes the tragic fate of the protagonist. The study also considers the scholarly interpretations of the “little man” in literary criticism and demonstrates the continuity and transformation of this literary phenomenon in different historical periods. The findings confirm that the image of the “little man” remains one of the most significant and enduring themes in Russian literature, reflecting changing social realities while preserving its core humanistic meaning.